2020
DOI: 10.1002/acr.23926
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent Hyperuricemia and Gout in Rheumatoid Arthritis: Associations With Comorbidities, Disease Activity, and Mortality

Abstract: ObjectiveAlthough hyperuricemia and gout can complicate the course of rheumatoid arthritis (RA), the impact of these factors on outcomes in RA is unclear. We undertook this study to examine associations of coexistent hyperuricemia and gout with RA disease measures, RA treatments, and survival.MethodsParticipants from a longitudinal RA study were categorized by the presence of gout and serum urate (UA) status. Groups were compared by baseline patient characteristics, RA disease activity, treatments, and comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
1
15
0
2
Order By: Relevance
“…Few studies suggested that a significant proportion of RA patient’s exhibit monosodium urate deposition consistent with gout, challenging the previous perceptions that gout and RA are mutually exclusive conditions. 45…”
Section: Discussionmentioning
confidence: 99%
“…Few studies suggested that a significant proportion of RA patient’s exhibit monosodium urate deposition consistent with gout, challenging the previous perceptions that gout and RA are mutually exclusive conditions. 45…”
Section: Discussionmentioning
confidence: 99%
“…Gout is a self-limited in ammatory joint disease which pathogenesis is complex and it attack is the outcome of combined action of multiple factors.Such as excessive intake sea food or alcohol is considered the predominant risk factor of gout,and the result from Horvathova V et al revealed that [15] as the increase of the age,the risk of gout is also increasely and the gout patients compare to healthy individuals have higher BMIs.Studies have shown that [16][17][18] there are close correlations between gout and kidney disease,obesity,hypertension,diabetes mellitus,cardiovascular and cerebrovascular diseases and so on.Our analysis showing that BMI,DBP,SUA,GLU,BUN,CREA,TG,HDL-C and LDL-C are the risk factors of gout which in line with most of the research conclusion [19][20] .However,in particular,gout is a polygenic hereditary disease and genetic factors are still play crucial role in gout.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid, the main bioactive phytochemicals in coffee, belongs to the polyphenol family and has been reported to have anti-gout activity, elicited via its anti-inflammatory effects [ 46 ]. Gout is a form of inflammatory arthritis that is highly associated with RA patients [ 47 ]. Triptolide shows inhibitory effects by decreasing IL-18 and IL-18 receptors in rheumatoid arthritis synovial fibroblasts stimulated by phorbol 12-myristate 13-acetate (PMA) [ 48 ].…”
Section: Anti-inflammatory Activity Of Phytochemicals In Prevalentmentioning
confidence: 99%